Black friend : essays - Ziwe (Abrams Image, 2023)
"Ziwe made a name for herself by asking guests like Alyssa Milano, Fran Lebowitz, and Chet Hanks direct questions. In Black Friend, she turns her incisive perspective on both herself and the culture at large. Throughout the book, Ziwe combines pop-culture commentary and personal stories, which grapple with her own (mis)understanding of identity. From a hilarious case of mistaken identity via a jumbotron to a terrifying fight-or-flight encounter in the woods, Ziwe raises difficult questions for comedic relief"--